THE SOUTH CHINA SEA CONFLICT AND TRANSFORMATION FOR ENERGY SECURITY IN THE SOUTHEAST ASIA REGION - Farhan Dilan Ramadhan (JLAST : Journal of Law and Social Transformation, 2026)
Energy Security can be described as a concept that ensures the amount of energy supply needed by a country is sufficient to encourage development and maintain the welfare of its people. The purpose of this study is to analyze the implications of conflicts that occur in the South China Sea region on countries around the region to obtain and fulfill their country's energy security. The method used in this research is a qualitative method based on the Regional Security Complex theory. The results of this research indicate that the ongoing conflict in the South China Sea region is a hindrance for the surrounding countries to explore the natural resources stored in the region.